Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah pada NH Cake - Christine Monica Saren; Angelin Marla Halawane (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
Financial reports are tools that provide information on the financial position, performance, and changes in the financial position of a company that are beneficial for many users in making economic decisions so that the financial performance of their business can grow. This study aims to determine how the implementation of SAK EMKM is in the HN Cake business. This type of research uses a qualitative research method with a descriptive approach. Based on the results of this study, it shows that the NH Cake business has not fully implemented SAK EMKM in its business, the bookkeeping carried out is only based on cash in and cash out.